Enterococci isolated from Cypriot green table olives as a new source of technological and probiotic properties - Anagnostopoulos, Dimitrios A.; Bozoudi, Despina; Tsaltas, Dimitrios (My University, 2018)
Table olive is one of the main fermented vegetable worldwide and can be processed as treated or natural product. Lactic Acid Bacteria (LAB) are responsible for the fermentation of treated olives. The aim of this work was to study the technological characteristics and the potential probiotic properties of LAB isolated from Cypriot green table olives. This is the first comprehensive report on the isolation and characterization of LAB isolates retrieved from Cypriot green table olives. From a collection of 92 isolates from spontaneously fermenting green olives, 64 g positive isolates were firstly identified to genus level using biochemical tests, and secondly to species level using multiplex species specific polymerase chain reaction (PCR) amplifications of the sodA gene. Moreover, each of our isolates were tested for their technological and probiotics properties, as well as for their safety characteristics, using biochemical and molecular methods, in order to be used as starter cultures. Finally, to discriminate the most promising isolates on the base of their technological and probiotics properties, Principal component analysis was used. All the isolates were identified as Enteroccocus faecium, having interesting technological properties, while pathogenicity determinants were absent. Principal component analysis showed that some isolates had a combination of the tested parameters. These findings demonstrate that enteroccoci from Cypriot table olives should be considered as a new source of potential starter cultures for fermented products, having possibly promising technological and probiotic attributes.
Keywords: Enterococcus spp; Lactic Acid Bacteria; Probiotics; Table olives; Technological characteristics